Analysis of Heavy Metals Concentration in Fish and Crustaceans from Muar River - Abdul Razak, Nurul Ashykin; Abdullah, Shakila (Enhanced Knowledge in Sciences and Technology, 2021)
Contaminations of the aquatic environment may enter the food chain and pose health risks to the population. This study aims to determine the heavy metals concentrations in the Muar River and to assess the health risk for the population. The analysis of heavy metals concentration was analyzed using the Atomic Absorption Spectroscopy (AAS) by using microwave digestion technique. The hierarchy of the heavy metals in seabass (Lates Calcarifer) is Zn > Cd > Cu > Pb > Cr > Fe while in prawn (Penaeus sp.), is Zn > Cu > Cd > Pb > Cr > Fe and in oyster (Crassostrea sp.). is Cd > Zn > Cu > Cr > Fe > Pb. All of these metals concentrations were below the maximum permissible limits set by Malaysian Food Act (1983) and Regulations (1985). Target Health Quotient (THQ) value based on the studied metals shows that seabass, prawn, and oyster were below 1, which indicates that the consumptions of the fish and crustaceans from Muar River are safe for human consumption and health